Measurements of prompt charm production cross-sections in pp collisions at s√=5 TeV - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (Springer, 2017)
Production cross-sections of prompt charm mesons are measured using data from pp collisions at the LHC at a centre-of-mass energy of 5TeV. The data sample corresponds to an integrated luminosity of 8:60 ± 0:33 pb^-1 collected by the LHCb experiment. The production cross-sections of D0, D+, D+s, and D*+ mesons are measured in bins of charm meson transverse momentum, pT, and rapidity, y. They cover the rapidity range 2:0 < y < 4:5 and transverse momentum ranges 0 < pT < 10 GeV=c for D0 and D+ and 1 < pT < 10 GeV=c for D+s and D*+ mesons. The inclusive cross-sections for the four mesons, including charge-conjugate states, within the range of 1 < pT < 8 GeV=c are determined to be σ(pp → D0X) = 1004 ± 3 ± 54 μb; σ(pp → D+X) = 402 ± 2 ± 30 μb; σ(pp → D+s X) = 170 ± 4 ± 16 μb; σ(pp → D*+X) = 421 ± 5 ± 36 μb where the uncertainties are statistical and systematic, respectively.